IDEA-DETAILS TO ENHANCE NARRATIVE WRITING ACHIEVEMENT - TASYKIRAH, FITRIAH; INDERAWATI, RITA; IHSAN, DIEMROH (Sriwijaya University Learning and Education International Conference, 2016)
Teacher is the creator and designer, the one who creates the design of media that will be used during the learning process. Teaching media for language learning especially in writing skill is needed since writing is the most difficult skill to be acquired. One of media for improving writing skill is picture-based media. In this case,Multifunctional Folklore Card (MFC), a medium designed and created for English learning by Bella, Rizqiyah, Tasykirah, Andani, Pangestu and Inderawati (2015), offers picture-based for writing skill learning particularly in narrative text. The term multifunctional in this media refers to its functions to be applied for improving studentsâ English skill. MFC is a game; learning media with the focus on narrative since one of the materials for MFC is folklore (traditional story) of which features are character- match card, sequence card, and vocabulary card. A study of MFC has been conducted by Bella et al. (2015), it focused on vocabulary achievement from students of MTs Ilham Palembang which let students to match similar meaning between local language and English. Besides using media for writing skill improvement, Idea-Details strategy also helps the learners to organize their narrative writing from MFC picture cards into a complete narrative text paragraph with the table of pre-writing activity on idea and details from those pictures.This paper aims to elaborate the use of MFC as a medium in narrative writing skill improvement and the use of Idea-Details as the strategy in helping students to organize their narrative text writing